مەترسی پیشەیی لە پیادەكردنی كاری كۆمەڵایەتیدا توێژینەوەیەكی مەیدانییە لە شاری سلێمانی - فرج, چرۆ محمد (Sulaimani Journal for Humanities, 2025)
The present research studied the professional risk in humanity professions particularly in practicing social work. This research guided by the processes of descriptive-analytical research through using the methods of history, survey and comparative. this research’s main aim was to know and identify the professional risk in general and according to institution’s type, sex, age, marital status, certification, Field and service time period of all the humanities practitioners (social & psychological) that practice social work in (4) different type institution included the number of formal-governmental institutions (which they proved various and different help services to those in need). They had been chosen in an intensive way in the city of Sulaimani. Simi structured interview conducted that contained (21) closed, open and Simi closed questions as the appropriate tool in accordance with the subject, the community and the sample of the research, and then the interviews had been done in accordance with the will, permission and time of (54) practitioners that wanted to participate in the research, the interviews lasted between one and a half to two hours within (4) months. In order to identify the results statistically paired sample T-test and Mean with percentage had been used. The results concluded that all the practitioners involved in the research were face professional risk in different degree, level and rate. The type, rate, level, degree and dealing with professional risk were equal with the type, rate and level of the problem of service user and the type of the institutions (Which was physical, psychological, social and legal risks). There were no difference according to sex in face and work on the cases of professional risk, but professional risk was the reason of male practitioners to leave working on the cases. There were no difference according to specialty between social and psychological fields regarding face, work and leave the work on the cases of professional risk. There were differences according to age, marital status, certification and the service time period of practitioner in face, work on and leaving the work on the cases of professional risk.